Appraisal of post-downsizing stress and survivor's work attitude - Noorfiza, Sani (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study was motivated by the reality of employee downsizing that is obvious since it brought many proven negative consequences on whole business landscape, organizational and individual employees. The major challenge was to manage human resource or the remaining employees (survivor) after layoff as their work attitudes were diminishing to remain effective in an organization. The purposes of the study are to examine whether four independent variables of the appraisal of post-downsizing stress (job insecurity, role ambiguity, role conflict and role overload) and the moderator role of perceived organizational support as coping mechanisms of the harmful effects of employee downsizing were significant factors and effective predictors of survivor's work attitude.